Penerapan Etika Islam Pada Program IICP (Internasional Islamic Classs Program) TIngkat SMP di Pondok Pesantren Puncak Darussalam Patoan Daya Pamekasan Madura - Jihan Amalia Syahidah, Jihan (Mahad Aly Al Fithrah, 2021)
Islamic ethics in the life of the millennial generation is considered to be something important to apply. Advances in technology and open access to information make modernization unavoidable. Therefore, Islamic ethics is considered a shield for the millennial generation in carrying out their actions in everyday life. Strengthening Islamic ethics is also what the IICP (International Islamic Class Program) program for junior high school level at Pondok Pesantren Puncak Darussalam Patoan Daya Pamekasan, Madura is trying to implement. The approach used in this study is a qualitative approach with the aim of knowing how Islamic ethics is applied in the IICP program (International Islamic Class Program) at Ponpes Puncak Darussalam by using document study methods, observation, and interviews with several informants so that data triangulation can then be carried out to produce valid data. The results of the study show that Islamic ethics in the IICP program for SMP Ponpes Puncak Darussalam has been implemented well. The support from the caregiver, namely Kyai Abdul Hannan Tibyan and the ustadz as well as several activities aimed at cultivating the morality of the students, are expected to be the first step to creating Islamic ethics in the IICP program environment at the junior high school level considering that this program is a program that is expected to be a program international standard. However, in the implementation of the application of Islamic ethics in the IICP program, several obstacles were found so that more support was needed from caregivers, ustadz, and from within the students themselves to get used to doing commendable morals and avoiding despicable morals in accordance with the teachings of the Qur'an and Hadith.